HR Flexibility in Family Firms: Integrating Family Functioning and Family Business Leadership. (2nd October 2019) - Goel, Sanjay; Xiu, Lin; Hanson, Sheila; Jones, Raymond J.
ABSTRACT: We developed a conceptual model that links central constructs of family functioning to HR flexibility and subsequent HR outcomes in family businesses. We proposed that family functioning was associated with two fundamental leadership decisions (i.e. family-business integration and family involvement) in family businesses. We posited that family business leaders have immense discretion to make these critical decisions that establish the degree to which the family firms would exhibit HR flexibility. We distinguished the three dimensions of HR flexibility – skill, behavioral, and HR practices flexibility and proposed that skill and behavioral HR flexibility generally lead to positive HR outcomes whereas the effects of HR practice flexibility on HR outcomes would be moderated by whether the employee is a family or non-family employee.